Pengaruh emotional freedom technique terhadap kualitas tidur pasien hipertensi di wilayah kerja upt puskesmas kuta utara tahun 2021 : Effect of emotional freedom technique on sleep quality of hypertensive patients in upt puskesmas north kuta working area in 2021 - I Wayan Candra; Utami, Gusti Ayu Septian Maya Dwi; Sumirta, I Nengah; Sulisnadewi, N.L.K (Bali Medika Jurnal, 2021)
Hypertension is a non-communicable disease that continues to receive attention in an effort to improve public health status. Some people are not aware of having hypertension and often do not show symptoms, only realizing it after causing organ disorders. The condition of hypertension that is not managed according to standards can have various adverse effects on the quality of a person's life. One of them can be caused is disturbing the quality of a person's sleep.The purpose of this study is to determine the influence of Emotional Freedom Technique on the sleep quality of hypertensive patients. Design research using  one-group pre-post test design. Sampling techniques used  nonprobability sampling  is  purposive sampling. The number of samples as many as 19 people. The research instrument used is the Pittsburgh Sleep Quality Index  (PSQI). The results showed the quality of sleep of hypertensive patients before being given emotional freedom technique,  namely all research subjects as many as 19 people (100%) poor sleep quality. After being given  Emotional Freedom Technique  showed the quality of sleep hypertension patients to be good as many as 6 people (31.6%). There is an effect of Emotional Freedom Technique on the Sleep Quality of hypertensive patients (p=0.000). Emotional Freedom Technique  improves the sleep quality of hypertensive patients.